O ator do teatro da escrita no palco entre a tradição e a modernidade: metamorfoses do teatro imaginado como forma de absorção do moderno e do cosmopolita - Thürler, Djalma (2006)
The writing theatre s actor on stage between tradition and modernity the imagined theatre s metamorphosis as a way of absorbing the modern and the cosmopolitan is the result of a consideration about the actor s place in the present of 2006 and in what refers to its substantive aspects, its fundamental nucleus consists of tracing, on the whole, the role which will be up to the actor during the post modernity, this empty world, of drifting fragments, made of simulacrum, of images, of empty surfaces without any historic or human thickness, a dramaturgy still to be written, which goes through several routes: from the condition of mere pictorial element, implication of the painted canvas, the actor became three-dimensional and, being in possession of his own will, took his art to the streets defying the job market and refusing to be a simple labor on the theatre company. Afterwards, the cheerful mock converted the legacy into anti-art giving artistic value to the daily banality which neither represents nor interprets anymore, but presents life, afterwards, the postmodern establishes the complete glorification of the ego at the moment, without hope of any in the future, it does not have a defined identity, it does not distinguish true from false. The different styles coexist, the tendencies quickly succeed to each other. There are a few groups or unified movements, pluralism and eclecticism are the rule which deflates all the stable ordered up to that time, preventing a possible separation between this and that; the review of the artistic and aesthetic knowledge legitimating criteria obliges us, in a closer or farther future, it does not matter, to live with the mutations, transformations and changes that will still happen